Role of polycystic ovarian syndrome in developing psychological burden in Saudi Arabian females: A case control study - Alamri, Abdulhakeem S.; Alhomrani, Majid; Alsanie, Walaa F.; Almuqbil, Mansour; Alqarni, Khawlah M.; Alshehri, Saleh M.; Abdulaziz, Osama; Salih, Magdi M.; Raafat, Bassem M.; Alamri, Abdulwahab; Alomar, Nasser Fawzan; Asdaq, Syed Mohammed Basheeruddin (Frontiers in Public Health, 2022)
It is well known that polycystic ovarian syndrome (PCOS) may elevate psychological problems in patients, but there is a scarcity of the studies among Saudi Arabian population. This research was designed to investigate the influence of PCOS on the development of psychological load in terms of depression, anxiety, and stress in comparison to normal women who have no PCOS. Further, a correlation of psychological distress in PCOS females was done with their educational level. This is case-control research carried out in one of Riyadh's multispecialty hospitals. In the PCOS patients and control groups (each with 84 samples), samples were collected using convenience sampling and a simple random approach, respectively. The psychological burden was determined using DASS-21. The data obtained were analyzed using SPSS-IBM 25. Most participants (52.9%) were between the ages of 26 and 35 and had a university education (68.4%). A significantly higher percentage of PCOS patients (P = 0.001) had irregular menses, hirsutism, infertility, and acne in comparison to the mothers without PCOS. There was a significantly higher possibility of depression (P = 0.003), anxiety (P = 0.016), and stress (P = 0.001) among PCOS patients than in control subjects. Among the psychological domain tested in the study, the risk of developing stress (odds ratio, OR = 8.32) was high when compared to depression (OR = 3.12) and anxiety (OR = 2.127) in PCOS patients. Furthermore, when compared to PCOS females with less education, a significantly lower number of university-educated PCOS females developed depression. The study demonstrates a high prevalence of psychological burden among the PCOS population. Higher education has been shown to help in alleviating depression in PCOS females. Meeting PCOS women's psychological needs will improve their overall health status.